Sibling rivalry among anti-corruption agencies in Taiwan. Issue 1 (5th January 2015) - Jon S.T. Quah, Dr; Chilik Yu, Professor; Ko, Ernie; Su, Yu-Chang; Yu, Chilik
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide insights into the multiple anti-corruption agencies (ACAs) in Taiwan and their conflict resolution. The birth of the Agency Against Corruption (AAC) in 2011 created the unintended consequence of sibling rivalry with the elder Ministry of Justice Investigation Bureau (MJIB). Design/methodology/approach – A historical background of these agencies is discussed and followed by an analysis of the diversified conflicts among the prosecutor's office, the AAC and the MJIB. The empirical sources of this study include 17 in-depth interviews with government officials both at ministerial level and field level, scholars and NGO representatives. Findings – The redundancy of ACAs in Taiwan is a fact, which is extremely difficult to change in the foreseeable future in the light of current political and fiscal constraints. This paper concludes that the conflicts among multiple ACAs and their operational weaknesses will not fade away after a mere directive from their superior, the Ministry of Justice, unless genuine cooperation is put into place in various individual cases. Practical implications – This paper provides a road-map for decision makers to improve collective anti-corruption performance. Taiwan's AAC serves as the latest example testing the efficacy of the multiple specialized ACAs. Originality/value – This pioneering study provides insights into Taiwan's anti-corruption policy and practices. More investigative studies should be conducted on the effectiveness of multiple ACAs in other countries.